Analisis Kepemimpinan Kepala Sekolah dalam Meningkatkan Mutu Pendidikan - Yetri Nubatonis; Todi Benu; Endang Oekolos³; Merry Toineno; Sandi Ninomna; Yanti Y.E Sole (Jurnal Ilmiah Literasi Indonesia, 2026)
This study seeks to examine the influence of school administrators' leadership on enhancing teachers' performance, identify the initiatives undertaken, and uncover the facilitating and obstructive elements.  The used methodology is a qualitative technique grounded on literature review and descriptive analysis, including the synthesis of diverse pertinent information sources, including books and scholarly papers. The research findings indicate that the principal has a pivotal function as an educator, manager, administrator, supervisor, leader, innovator, and motivator (EMASLIM). Initiatives to enhance teacher performance are implemented via academic monitoring, incentive, professional development, and the establishment of a supportive school culture. The primary facilitating variables consist of a favourable organisational atmosphere and the proficiency of the school administrator, while the obstructive aspects include excessive administrative responsibilities, opposition to change, and constraints in facilities and infrastructure.